Ten Reasons Why Canada Should Join the American Convention on Human Rights - Duhaime, Bernard (Revue générale de droit, 2019)
The present contribution seeks to present comprehensively ten reasons why Canada should join the American Convention on Human Rights and recognize the compulsory jurisdiction of the Inter-American Court of Human Rights.